Development of an aerogenous Escherichia coli infection model in adult broiler breeders - Sofie Kromann (Nature Portfolio, 2021)
Abstract Escherichia coli constitutes an immense challenge to the poultry industry due to its devastating effect on productivity, mortality, and carcass condemnations. To aid future studies on disease mechanisms and interventions, an aerogenous infection model was established in adult broiler breeders. Hens (n = 120) were randomly allocated into six groups receiving either aerosolised E. coli or vehicle, or intratracheal E. coli or vehicle. Replication of aerosol inoculation was performed on distinct days. Alternating euthanasia time points were predetermined in order to evaluate the progression of the disease. All animals were thoroughly necropsied, and bacteriological samples were collected as well as tissues for histopathology. Birds inoculated with E. coli exhibited clinical signs and developed characteristic gross and histopathological lesions of colibacillosis, including splenic fibrinoid necrosis, folliculitis, polyserositis and impaction of parabronchi with fibrinoheterophilic exudate and necrotic debris, as well as positive in situ localisation of intralesional E. coli by immunohistochemistry. This study presents a successful development of a discriminative colibacillosis model through aerosol inoculation of adult broiler breeders. Gross and histopathological lesions characteristic of colibacillosis were established in two independent experiments.